2019
DOI: 10.1016/j.isjp.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Composite grafts for fingertip amputations: A systematic review protocol

Abstract: HighlightsThere is a lack of evidence for composite grafting for distal finger tip amputation.We present a systematic review protocol on the use of composite grafts.This review will aim to provide clinicians with more guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Only two articles were able to find statistically significant correlations where a lower age of patients (<4 years) leads to better outcomes. 5,6 Borrelli et al also found a correlation between injury mechanism and graft take, where composite grafts performed after crush injuries were more likely to survive. 5 This is concordant with the results observed in our study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Only two articles were able to find statistically significant correlations where a lower age of patients (<4 years) leads to better outcomes. 5,6 Borrelli et al also found a correlation between injury mechanism and graft take, where composite grafts performed after crush injuries were more likely to survive. 5 This is concordant with the results observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 Borrelli et al also found a correlation between injury mechanism and graft take, where composite grafts performed after crush injuries were more likely to survive. 5 This is concordant with the results observed in our study. We observed an association of higher composite graft survival with a lower time to operation, but this was based on small number of studies and fingertips.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations